Pengembangan Analisis Laporan Keuangan untuk Meningkatkan Literasi Keuangan dan Efisiensi Operasional UMKM - Arsjah, Regina Jansen; Rayi Retno Dwi Asih; Lenggogeni (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to enhance financial literacy and improve MSME owners’ skills in preparing and analyzing financial statements as a basis for business decision-making. The activities involved structured training and technical assistance for 40 MSME participants from Bekasi and Jakarta. The training materials included basic financial statements (balance sheet, income statement, cash flow) and simple financial ratio analysis. Evaluation was conducted using pre-tests, post-tests, and observation of practice sessions. The results indicated that 80% of participants were able to independently prepare financial statements, while 85% reported improved understanding of cash flow management and cost control. Some MSMEs also applied the Material Flow Cost Accounting (MFCA) approach to identify production efficiency, reducing raw material waste by up to 10%. This program demonstrates that practice-based financial literacy training can strengthen transparency, increase financial institutions’ trust, and support the sustainability of MSMEs.